(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article is dedicated to the scientific analysis of the lexical-semantic characteristics of idioms related to human body parts in the Uzbek language. Idioms reflect the culture and social relationships of the people, expressing various emotions and traits. The analysis categorized idioms based on metaphorical and metonymic meanings, exploring their connection to Uzbek cultural values. The results illustrate how idiomatic expressions convey social and ethical norms, contributing to the enrichment of the idiomatic richness of the Uzbek language.